Determinantes de competitividade de destinos turísticos aplicados aos roteiros regionais: uma avaliação do roteiro Seridó/RN - Batista, Saulo Gomes (2013)
The tourism industry is gaining representation by move and stimulate the economy, especially by allowing the generation of employment and income, thus allowing growth opportunities for localities where tourism develops. Therefore, the present study entitled determinants of competitiveness of tourist destinations applied to regional routes: an evaluation of the Route of Seridó/RN, discusses the issue of competitiveness in tourism and tries to understand the scenery of this Route. The main objective of the study is to assess the conditions of competitiveness in the Route of Seridó/RN according to benchmarks and global determinants of competitiveness for tourist destinations. The study has also as specifics objectives: define dimensions of the reference model for use in evaluating the competitiveness of the Route of Seridó/RN; identify levels of governance and competitiveness in the municipalities that make up the sample set above the Route, and analyze to what extent the competitiveness of the Route correspond to the global reference of competitiveness of tourism destinations. Regarding the methodology, it is a search for an exploratory- descriptive and used a combination of quantitative and qualitative research method as expected and required in the implementation of the evaluation tool called Compet&enible Model. For data collection, it has been taken technical visits and also analysis of documents and materials. Data analysis was based on the records and documents and the use of simple descriptive statistics for the scores of the elements offered by Compet&enible Model. The results allowed us to know the real conditions of competitiveness of the Seridó/RN Route forward to the attributes of tourist destinations for global competitiveness: the dimension I, Governance, reached 17 points, classified as "in structuring" and dimension II, Competitiveness, reached 10 points, ranking "weak". These results highlight the need for greater involvement of the actors in the supply chain of tourism in Polo Seridó/RN for the actions, programs and projects are put into practice. It is expected that tourism is considered an important activity for the local and global development, serving as a reference for the future management of Seridó/RN Route, guiding new policy guidelines, planning and organization to better competitiveness